2014
DOI: 10.1210/jc.2013-4518
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Dose Estrogen Replacement During Childhood on Pubertal Development and Gonadotropin Concentrations in Patients With Turner Syndrome: Results of a Randomized, Double-Blind, Placebo-Controlled Clinical Trial

Abstract: In addition to previously reported effects on cognitive measures and GH-mediated height gain, childhood estrogen replacement significantly normalized the onset and tempo of puberty. Childhood low-dose estrogen replacement should be considered for girls with Turner syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 59 publications
0
38
0
2
Order By: Relevance
“…The initial dose of EE 2 , 1-5 ng/kg in group E, was extremely low even in comparison with the dosage of 25 ng/kg reported in a previous study [10,11]. Additionally, this is the first study ##, ### A significant difference as described in the text.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…The initial dose of EE 2 , 1-5 ng/kg in group E, was extremely low even in comparison with the dosage of 25 ng/kg reported in a previous study [10,11]. Additionally, this is the first study ##, ### A significant difference as described in the text.…”
Section: Discussionmentioning
confidence: 57%
“…It is well known that not only BMD acquisition but also bone maturation is estrogen-dependent [19]. In a recently published report by Quigualy et al [10], where the initial dose of EE 2 was 25 ng/kg, breast development was observed in some of the patients. This pubertal The mean and SD are shown.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…One double-blind, placebo-controlled trial using ultra-low-dose oral ethinylestradiol as a growthpromoting agent during the prepubertal period combined with GH demonstrated a modest synergistic increase in AH, normalization of the timing of thelarche for about one-quarter of the girls, and modest improvements in cognition and memory within specific developmental windows (87,143,144,145).…”
Section: Concomitant Treatment With Childhood Ultra-low-dose Estrogenmentioning
confidence: 99%